2011
DOI: 10.1002/crat.201100038
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired synthesis of morphologically controlled SrCO3 superstructures by natural gum acacia

Abstract: Crystallization of strontium carbonate is performed in aqueous solution using Gum Acacia (GA) as crystal growth modifier. A novel study of hierarchical assembly, specifically interacting inorganic and natural component without introduction of other additives was studied. SrCO 3 structures exhibiting the morphologies of well defined nanocrystallites in the form of clusters of hexagonal rods, flower shaped, cross like, doughnut shaped and rice grain shaped are identified by optimizing the conditions and concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…make an incorrect conclusion that the SrCO 3 crystal grows mainly along the (111) face 41,44 . However, such XRD pattern (at ~ 25.5° in Fig.…”
Section: Preferred Growth Orientation Of Srcomentioning
confidence: 99%
“…make an incorrect conclusion that the SrCO 3 crystal grows mainly along the (111) face 41,44 . However, such XRD pattern (at ~ 25.5° in Fig.…”
Section: Preferred Growth Orientation Of Srcomentioning
confidence: 99%
“…12,[33][34][35][36] Like CaCO 3 and BaCO 3 , various and interesting morphologies of SrCO 3 also have been fabricated, such as rods, fibers, spheres, ellipsoids, and ribbons. 10,[37][38][39] For CaCO 3 , it is not easy to prepare pure aragonite without any other polymorph; however, BaCO 3 and SrCO 3 have only one polymorph, named witherite and strontianite, respectively. 10 Interestingly, both of them have the aragonitic crystal structure.…”
Section: Introductionmentioning
confidence: 99%
“…In degenerate planar bending [51] . (Figure 5a), 1440.51 cm -1 (Figure 5b), 1438.59 cm -1 (Figure 5c), 1452.05 cm -1 (Figure 5d) and 1452.84 cm -1 (Figure 5e) In our previous study on as-synthesized BaCO 3 nanocrystallites using natural gum acacia [52] , it was observed that the evolution of gas in the first two steps…”
Section: Synthesis Of Baco 3 Microstructuresmentioning
confidence: 73%